O comportamento diante do paradigma behaviorista radical - Carrara, Kester [UNESP]; Zilio, Diego [UNESP] (My University, 2015)
The matter of defining behavior figures scientific literature of diverse areas of knowledge for over a century, but an agreement about the fundamental aspects related to the topic was not reached yet. The main discussions usually identify behavior with diverse terms such as activity, action, relation, event and interaction. This article brings into discussion some aspects of the historical context related to the evolution of the term ‘behavior’. Furthermore, it discuss some implications of adopting the main definitions available and, in doing so, it also provides an analytical framework that we hope may be useful to behavior analysts in making consistent and contextualized choices on the definition of behavior, especially in the domain of operant behavior as formulated by radical behaviorism.

A questão da definição de comportamento frequenta a literatura científica de diversas áreas do conhecimento há mais de um século, sem que os pesquisadores tenham estabelecido acordo sobre aspectos fundamentais envolvidos no tema. As principais discussões estão vinculadas à identificação ou não do termo com atividade, ação, relação, evento e interação. Este artigo recupera parte do contexto histórico de evolução do termo, aponta implicações derivadas de se optar por alguma dentre as principais definições disponíveis e elabora um cenário analítico que – espera-se – possa contribuir com a comunidade de analistas do comportamento para realizar escolhas consistentemente contextualizadas de uma definição de comportamento especialmente direcionada ao âmbito do comportamento operante tal como formulado pelo Behaviorismo Radical.
Behavior under the paradigm of radical behaviorism
Keywords: Behavior; Behaviorism; Behavior analysis; Comportamento; Behaviorismo; Análise do comportamento